2019
DOI: 10.1007/s00330-019-06381-8
|View full text |Cite
|
Sign up to set email alerts
|

Radiomic feature reproducibility in contrast-enhanced CT of the pancreas is affected by variabilities in scan parameters and manual segmentation

Abstract: Objectives-To measure the reproducibility of radiomic features in pancreatic parenchyma and ductal adenocarcinomas (PDAC) in patients who underwent consecutive contrast enhanced computed tomography (CECT) scans.Methods-In this IRB-approved and HIPAA-compliant retrospective study, 37 pairs of scans from 37 unique patients who underwent CECTs within a two-week interval were included in the Terms of use and reuse: academic research for non-commercial purposes, see here for full terms. http://www.springer.com/gb/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
41
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 37 publications
3
41
0
2
Order By: Relevance
“…The reason for this high interobserver agreement may be explained by the high accuracy of the semi‐automated intensity tracing algorithm for this relatively simple task to segment the phantom from the image background. In our results, it seemed that the repeatability of many radiomics features subjected more to acquisition variations than to segmentation uncertainty, which was in line with the findings recently reported in a few clinical studies 53,54 . But, this indication could still not be safely extended to generic radiomics use in MRgRT, in which target tumor and/or organs at risk (OARs) delineation relies heavily on manual segmentation, which might subject to considerable interobserver segmentation variability.…”
Section: Discussionsupporting
confidence: 87%
“…The reason for this high interobserver agreement may be explained by the high accuracy of the semi‐automated intensity tracing algorithm for this relatively simple task to segment the phantom from the image background. In our results, it seemed that the repeatability of many radiomics features subjected more to acquisition variations than to segmentation uncertainty, which was in line with the findings recently reported in a few clinical studies 53,54 . But, this indication could still not be safely extended to generic radiomics use in MRgRT, in which target tumor and/or organs at risk (OARs) delineation relies heavily on manual segmentation, which might subject to considerable interobserver segmentation variability.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, among the many confounding effects in radiomics such as scanner device, vendor, reconstruction method, image preprocessing and feature implementation, we only examined the influence of segmentation variability. Yamashita et al claimed that variations between scans had a higher impact on reproducibility than segmentation 17 . An additional aspect that was not covered in this work is the question as to what extent feature reproducibility translates into the reproducibility of a whole radiomic signature, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Zwanenburg et al 16 assessed radiomics feature robustness by image perturbation in computed tomography (CT) images. Yamashita et al 17 found that for contrast-enhanced CT images of patients with pancreatic cancer, scan parameters had stronger influence on radiomics features than segmentation variability. Tunali et al 18 assessed reproducibility of radiomic features extracted from peritumoral regions of lung cancer lesions.…”
mentioning
confidence: 99%
“…At present, the role of contouring in RFs reproducibility has been addressed in several studies [24][25][26][27], but to the best of knowledge, none of them concerned hepatic CRC metastases. Therefore, the aim of this work is to assess the influence of inter-reader contouring variability on the texture analysis of CRC liver metastases, focusing on the role of three-and two-dimensional segmentation in determining RFs robustness.…”
Section: Introductionmentioning
confidence: 99%